Anti‐migration and Combustion Catalytic Performances of Ferrocenyl Compounds of Anilines and Alkylamines Synthesized by Click Reaction. Issue 5 (20th October 2020) - Shi, Xiaoling; Cheng, Wenqian; Jiang, Liping; Bi, Fuqiang; Li, Jizhen; Zhang, Guofang
Abstract : To enhance anti‐migratory performance and combustion catalytic activities of neutral ferrocene‐based burning rate catalysts (BRCs), nine ferrocenyl 1, 2, 3‐triazolyl compounds of anilines and aliphatic amines (Fc‐ATAZs, 1 –9 ) were synthesized by click reaction and characterized by NMR, UV/Vis, FT‐IR, and MS. TG and DSC studies confirmed that the Fc‐ATAZs are highly thermal stable. Cyclic voltammetry results implied that 1 and 6 are reversible redox systems. The anti‐migration and anti‐volatility tests showed that the Fc‐ATAZs are low‐migratory and low‐volatile compounds.Combustion catalytic activity results of the Fc‐ATAZs revealed that they are highly active for promoting thermal disintegration of AP, RDX and HMX. Compounds 3, 2 and 8 can increase released heats of AP, RDX and HMX, respectively, by 132 %, 112 % and 36 %, respectively, being the highest in each case. Most of them are more active than the reported analogs derived from phenols and benzoic acids. They, except 9, are more active than catocene and can be used as potential BRCs in composite solid propellants. Abstract :